Thermogravimetric analysis: A new tool for dating human teeth - Rubio-Lamia, Leticia Olga; Delgado Ruiz, Alba; Lozano Peral, Diego; Suárez-Pérez, Juan; Martín-de-las-Heras, Stella (Elsevier, 2026)
Dating human skeletal remains is a major challenge in forensic science. The aim of this study is to correlate dating intervals related to the time elapsed since tooth extraction and the mass loss of human teeth, measured using thermogravimetry analysis in two different atmospheres: air and nitrogen. Forty healthy human teeth were stored for different periods after extraction (0, 10, 25, 50 years; N = 10/group) under controlled laboratory conditions. Thermogravimetric parameters (total percentage of mass loss, and percentage of mass loss in Step 1, Step 2 and Step 3) and derivatives of thermogravimetric parameters (temperature of maximum mass loss at Peak 1, Peak 2 and Peak 3) were quantified. Binary logistic regression and receiver operating characteristic (ROC) analyses were applied to assess the ability of these parameters to discriminate among the 10-, 25-, and 50-year intervals. Dating accuracy was consistently higher in air than in nitrogen atmosphere. Using thermogravimetric parameters, predictive formulas capable of distinguishing the different dating intervals with high precision were developed. The method achieved excellent performance to estimate 10-, 25-, and 50-year intervals in the air atmosphere, with areas under the ROC curves (AUC) ranging from 0.95 to 1.00. The results highlight thermogravimetric analysis as a promising technique for accurately estimating the time elapsed since tooth extraction in human teeth stored under controlled conditions.
Keywords: Odontología; Termogravimetría; Medicina legal; Antroprología forense; Human teeth; Forensic odontology; Forensic anthropology; Forensic medicine